Absence of population genetic structure in Heterakis gallinarum of chicken from Sichuan, inferred from mitochondrial cytochrome c oxidase subunit I gene. (2nd September 2016) - Gu, Xiaobin; Zhu, Jun-Yang; Jian, Ke-Ling; Wang, Bao-Jian; Peng, Xue-Rong; Yang, Guang-You; Wang, Tao; Zhong, Zhi-Jun; Peng, Ke-Yun
Abstract: Population genetics information provides a foundation for understanding the transmission and epidemiology of parasite and, therefore, may be used to assist in the control of parasitosis. However, limited available sequence information in Heterakis gallinarum has greatly impeded the study in this area. In this study, we first investigated the genetic variability and genetic structure of H. gallinarum . The 1325 bp fragments of the mitochondrial COX1 gene were amplified in 56 isolates of H. gallinarum from seven different geographical regions in Sichuan province, China. The 56 sequences were classified into 22 haplotypes (H1–H22). The values of haplotype diversity (0.712) and nucleotide diversity (0.00158) in Sichuan population indicate a rapid expansion occurred from a relatively small, short-term effective population in the past. The haplotype network formed a distribution around H1 in a star-like topology, and the haplotypes did not cluster according to their geographical location. Similar conclusions could be made from MP phylogenetic tree. The F st value ( F st <0.16965) and AMOVA analysis revealed that no significant genetic differentiation was observed among the seven different geographical populations. Neutrality tests (Tajima's D and Fu's Fs) and mismatch analysis indicated that H. gallinarum experienced a population expansion in the past. Our results indicated that H. gallinarum experienced a rapid population expansion in the past, and there was a low genetic diversity and an absence of population structure across the population.